If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 3q = -7 Solving 5p + 3q = -7 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3q' to each side of the equation. 5p + 3q + -3q = -7 + -3q Combine like terms: 3q + -3q = 0 5p + 0 = -7 + -3q 5p = -7 + -3q Divide each side by '5'. p = -1.4 + -0.6q Simplifying p = -1.4 + -0.6q
| -3(2-x)=x+8 | | 4(t-4)+8t=6(2t+4)-12 | | 6st-15t-10s-25= | | 2(4x+2)=-3x-9 | | 9n-26=-62 | | 37x+9=6(6x+7) | | 9x-1=4x+6 | | (X^2+2x+3)/(2x) | | 8d+d=180 | | 66x17/33x1/4 | | 2x^4+13x^2+20= | | 21x^4-4x^2-1=0 | | 4/13x=20 | | d(8)+d=180 | | 5y-2=3x-7 | | 2/-2 | | (x-3)=17 | | -(3y+3)-(2y-8)=-2 | | -10ik-2j+9k-6=-3j-k+9 | | x^5z^4/x^6z^3 | | (x-3)+(x+3)+(x+3)=17 | | 4(8x+24)=64 | | -(3y+3)-(-2-8)=-2 | | -5n-11=-46 | | x(31+-32)=629 | | 5/6x-4x+8/3=5/3 | | 2x-2y+z=2 | | x+31-x-31=629 | | 2x(5)+x(10)=640 | | 3x-2y+6z=12 | | 3x(2)+18x+15=0 | | 1.17x-0.2=0.5+0.66x |